Technological and bioactive properties of wheat glutenin hydrolysates prepared with various commercial proteases - Bozkurt, Fatih; Bekiroğlu, Hatice; Doğan, Kübra; Karasu, Salih; Sağdıç, Osman (Academic Press, 2021)
This study aimed to investigate the effect of different types of proteolytic enzymes (flavourenzyme, savinase, subsitilin, and savinase) on the technological and bioactive properties of glutenin hydrolysate. The degree of hydrolysis (DH) of the glutenin proteins significantly differed according to the enzyme types (p < 0.05). SDS patterns showed that the number and density of the bands decreased as the DH increased and the lowest molecular weight peptide fractions was observed in savinase and subsitilin hydrolysates. In general, hydrolysates with low DH had superior technological properties (oil absorption capacity, hydrophobicity, emulsifying activity, and stability index) compared to the higher ones. After enzymatic hydrolysis, the β sheet (%) of the hydrolysates increased, and the β turn (%) decreased compared to the control sample. The antioxidant capacity of the glutenin significantly increased by enzymatic hydrolysis (p < 0.05). The highest ABTS radical scavenging activity and FRAP activity was found in savinase and subsitilin hydrolysates with relatively higher DH. All hydrolysates exhibited an anti-diabetic effect depending on the DH. The anti-diabetic activity of the hydrolysate increased with increasing DH value. Hydrolysate samples showed no cytotoxic effect on the HEK293 healthy cell line, whereas hydrolysates exhibited cytotoxic effects on MIA PaCa 2 and CaCo 2 cancer cell lines.
Keywords: Antidiabetic effect; Antioxidant capacity; Cytotoxic effect; Protein hydrolysate